Вождь краснокожих: новеллы / О.Генри ; худож. А. Шахгелдян - О.Генри (Библиотека школьника, 2000)
Экземпляры: ф.1 (2000) / Инвентарный номер: 42553 / Сис.шифр: 84(7Сое)-7 / Авт.знак: Г 34 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)-7